What do the upwardly mobile think they deserve, and why? A multi-method investigation. (February 2020) - Simpson, Brent; Melamed, David
Abstract: We ask how upward intra-generational occupational mobility affects the incomes people believe they deserve, as well as their satisfaction with their current incomes. We argue that the upwardly mobile feel that they deserve lower incomes, relatively to those who experience no mobility or horizontal mobility, as a result of a relative deprivation process. We test this argument with two different studies. The first study uses representative data from the United States to demonstrate that upward occupational mobility is associated with depressed deserved incomes. The second study is an experiment designed to manipulate the experience of upward, downward and horizontal occupational mobility and to test the proposed causal mechanism. Results support the hypotheses, including the prediction that the impact of intra-generational upward mobility on satisfaction with one's income is mediated by a sense of relative deprivation. We conclude with a discussion of implications, including the role that experiments can play in research on stratification and mobility.